Organising Competition Using Online Form Technology as a Means of Increasing Chinese Students' Motivation in Learning RFL - Jiang Tao (Вестник Московского Университета. Серия 20: Педагогическое образование)
Background. The article discusses the need to improve the method of monitoring extracurricular activities in order to increase the motivation of Chinese students in the absence of a natural language environment.